2011
DOI: 10.1371/journal.pone.0023925
|View full text |Cite
|
Sign up to set email alerts
|

Early Second-Trimester Serum MiRNA Profiling Predicts Gestational Diabetes Mellitus

Abstract: BackgroundGestational diabetes mellitus (GDM) is one type of diabetes that presents during pregnancy and significantly increases the risk of a number of adverse consequences for the fetus and mother. The microRNAs (miRNA) have recently been demonstrated to abundantly and stably exist in serum and to be potentially disease-specific. However, no reported study investigates the associations between serum miRNA and GDM.Methodology/Principal FindingsWe systematically used the TaqMan Low Density Array followed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
212
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(233 citation statements)
references
References 48 publications
(59 reference statements)
3
212
0
3
Order By: Relevance
“…In addition, Pescador et al (2013) showed that three serum miRNAs (miR-138, miR-376a, and miR-15b) are potential biomarkers for distinguishing obese patients from obese-T2D and T2D patients; meanwhile, the combination of miR-503 and miR-138 can distinguish diabetic from obese-diabetic patients. Furthermore, Zhao et al (2011) found that three serum miRNAs (miR-132, miR-29a, and miR-222) can predict gestational DM with 66.7% sensitivity and 63.3% specificity (area under the curveZ0.642).…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…In addition, Pescador et al (2013) showed that three serum miRNAs (miR-138, miR-376a, and miR-15b) are potential biomarkers for distinguishing obese patients from obese-T2D and T2D patients; meanwhile, the combination of miR-503 and miR-138 can distinguish diabetic from obese-diabetic patients. Furthermore, Zhao et al (2011) found that three serum miRNAs (miR-132, miR-29a, and miR-222) can predict gestational DM with 66.7% sensitivity and 63.3% specificity (area under the curveZ0.642).…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…• Association between levels of some miRNAs and markers of microvascular impairment revealed the dysregulation of some in the serum and plasma of women who went on to develop GDM compared with the controls [43,44]. These results suggest that circulating miRNAs could be used as biomarkers for the early diagnosis or as a predictive factor for GDM.…”
Section: Circulating Mirnas As Early Predictive Biomarkers Of Diabetesmentioning
confidence: 90%
“…Furthermore, the miRNA content of different types of blood cells were also deregulated in type 1 and type 2 diabetic patients compared with controls [38][39][40][41][42]. Finally, analysis of circulating miRNAs in women with gestational diabetes mellitus has revealed that in both serum and plasma some miRNAs have an altered profile compared with those in control women [43,44].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 95%
“…Молекулярно-генетические механизмы этих нарушений изучены недостаточно. В ряде исследований была отмечена роль микроРНК в патогенезе ГСД [4] и ПЭ [5].…”
Section: актуальностьunclassified
“…Предполагается, что количественные измене-ния экспрессии некоторых микроРНК могут быть биомаркерами таких грозных осложне-ний беременности, как гестоз, гестационный сахарный диабет, хроническая плацентарная недостаточность и другие [5]. Так, значитель-ное снижение концентрации трех микроРНК (mir-29a, mir-222 и miR-132) были выявлены при сроке гестации 16-19 недель в крови бе-ременных, у которых в дальнейшим развился ГСД [4].…”
Section: актуальностьunclassified